Application of Role Playing Method to Increase Student Activity in Learning Indonesian Class II SDN 2 Gowak - Laela Nadhia Husna (Prosiding University Research Colloquium, 2021)
This study aims to increase student activity in Indonesian language subjects through theapplication of the Role Playing method. The research method used is Classroom ActionResearch (CAR). The subjects of the study were the second grade students of SDN 2 Gowak,totaling 10 students consisting of 4 male students and 6 female students. The resultsshowed that the activeness of students increased from the first cycle and second cycle. Inthe initial data, there are no students who have a very active category, students with anactive category are 10%, a moderately active category is 30% and a less active category is60%. After taking action in cycle I with the Role Playing method, the activity increased.Students in the very active category are 10%, the active category is 20%, the moderatelyactive category is 40% and the less active category is 30%. In the second cycle there wasan increase in the very active category 40%, the active category 40%, the moderately activecategory 20% and the less active category 0%. So it can be concluded that the Role Playingmethod is able to increase the activity of second grade students at SDN 2 Gowak.